f as a function of x is equal to the square root of quantity 5 x plus 7, g as a function of x is equal to the square root of quantity 5 x minus 7 Find (f + g)(x).

Respuesta :

Answer:

(f+g)(x) = [tex]\sqrt{5x+7}+\sqrt{5x-7}[/tex]

Step-by-step explanation:

f(x) = [tex]\sqrt{5x+7}[/tex]

and g(x) = [tex]\sqrt{5x-7}[/tex]

We need to find (f+g)(x)

(f+g)(x) = f(x) + g(x)

(f+g)(x) = [tex]\sqrt{5x+7}+\sqrt{5x-7}[/tex]

It can't be further solved so,

(f+g)(x) = [tex]\sqrt{5x+7}+\sqrt{5x-7}[/tex]

ACCESS MORE